(3GdEMJeGdGJ hGdEMUGA (B/s - (3THjLd, ehQGjs; (3TjdQ, Lhf s ((3GdbGgQI(B: s (3GdOGQ GdOhdjI ddESJKeGQGJ GdKbGajI(B, s, 2004)
(3CSGS GdGMJeGd, GdEMUGA GdhUaj, GdeJZjQGJ GdYThGFjI GdefaUdI,GdeJZjQGJ GdYThGFjI GdeSJeQI, CeKdI Ydi GdeJZjQGJ GdYThGFjI,fXQjI GdeYGjfI, fXQjI GdJbOjQ,GNJHGQGJ GdaQhV hGdeYfhjI,JegjO GdefMfjGJ hGdEfMOGQ hGdEQJHGW, JhRjYGJ GMJeGdjI CNQis
(3cTGa GdeUWdMGJ U(B.161-164s
Keywords: (3GdEMJeGdGJs; (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s